A 7-Year Retrospective Multisource Analysis on the Incidence of Anesthesia Awareness With Recall in Cancer Patients: A Chance of Collaboration Between Anesthesiologists and Psycho-Oncologists for Awareness Detection. Issue 5 (February 2016) - Cascella, Marco; Viscardi, Daniela; Schiavone, Vincenzo; Mehrabmi-Kermani, Farrokh; Muzio, Maria Rosaria; Forte, Cira Antonietta; De Falco, Francesco; Barberio, Daniela; Cuomo, Arturo
Abstract : Abstract: Although randomized controlled studies reported an incidence of anesthesia awareness with recall ∼1 to 2 per 1000 (0.1–0.2%), recent data from the NAP5 study showed an incidence of only 1:19, 600. Although in a prospective study many tools for anesthesia awareness detection can be used, a retrospective analysis requires a careful collection of information. The aim of the study was to evaluate the incidence of anesthesia awareness with recall in a cohort of cancer patients through a multisource retrospective analysis, and the clinical description, including the psychological outcome, of the cases detected. We also tested whether our retrospective analysis would be improved by a routinely psycho-oncological assessment. As secondary endpoints we evaluated the use of depth of anesthesia monitoring over a large cohort of patients, and the correlation between the brain monitoring and the incidence of awareness. We have carried out a 7-year retrospective analysis in a large cohort of cancer patients on the incidence of awareness with recall during general anesthesia. Of 35, 595 patients assessed for eligibility, 21, 099 were studied. We analyzed all data from the operative rooms' database, the anesthesia records, and from the database of the surgical divisions. In addition we examined reports from psychologists and spontaneous reports to the quality team of the hospital. Two certain cases of awareness were detected, with an incidence of 1:10, 550 (0.0095%). They occurred during elective surgery, in female patients without other risk factors. One case came from the report of a psychologist. In both episodes, brain monitoring was not applied and no long-term psychological sequelae were reported. Despite the limitations, our investigation suggests that the incidence of anesthesia awareness is very low, also in a specific cohort of patients, such as the cancer patients, and even when the depth of anesthesia monitoring is rarely used. The limitations caused by both the retrospective analysis and the absence of specific tools for direct awareness detection, such as structured interviews, can be filled with an effective postoperative psychological assessment which is often of routine in a cancer center. This observation could suggest the usefulness of inserting specific questions within the psychological tools commonly used by psycho-oncologists.